PENGARUH PENGANGGURAN, PENGELUARAN PEMERINTAH, PENDIDIKAN, RASIO KETERGANTUNGAN TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI 2011-2018 - Lestari, Ni Kadek Mega Dwi; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323], 2022)
This study aims to analyze the unemployment rate, government spending, education level, dependency ratio partially influence the poverty level in the Regency / City of Bali Province, and to analyze how much influence unemployment, government spending, education level, and dependency ratio simultaneously affect poverty. in the Regency / City of the Province of Bali. This research was conducted in regencies / cities in Bali Province, using secondary data methods and primary data to support this research. Methods of data collection using non-participant observation, documentation, and in-depth interviews as supporting methods. The analysis technique uses multiple linear regression. The results showed that unemployment, government spending, the dependency ratio partially had a significant positive effect on the poverty level, while the education level partially had a negative and significant effect on poverty. Simultaneously unemployment, government spending, education level, and dependency ratio have a significant positive effect on poverty.   Keywords: unemployment, goverment spending, education levels, dependency ratio, poverty